2017
DOI: 10.5539/ijel.v7n4p207
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into Stylistic Devices in Emily Dickinson’s and Sylvia Plath’s Poetry

Abstract: This paper focuses on the use of stylistic devices in Emily Dickinson's and Sylvia Plath's poetry. It differentiates between the phonological stylistic devices as alliteration, consonance and semantic stylistic devices as simile and personification. The study is carried out on five randomly selected poems from each poetess using the mixed modal research with the tool of tabulation to quantify the findings. Qualitative approach is used for analysis. The analysis provides a clear picture of the use of stylistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…The findings of this current research enriched and supported the findings of the study conducted by Zia (2017) and Bukhari and Asgher (2017). Zia (2017) revealed that there are 8 major levels of stylistics.…”
Section: Findings and Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The findings of this current research enriched and supported the findings of the study conducted by Zia (2017) and Bukhari and Asgher (2017). Zia (2017) revealed that there are 8 major levels of stylistics.…”
Section: Findings and Discussionsupporting
confidence: 88%
“…Meanwhile, Bukhari and Asgher (2017) showed that Sylvia has used more alliteration as compared to Emily. In contrast, the findings of this research showed that Walter Savage Landor"s "Acon and Rhodope; or, Inconstantly" used two major stylistics devices including grammatical categories in form of archaic words and figures of speech categories in form of imagery.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation